Leader-member exchange and creative idea validation: The role of helping and bullying - Ahmad Adeel; Samreen Batool; Kee Mui Hung Daisy; Zain-ul-Abdeen Madni; Muhammad Kamran Khan (Asian Academy of Management Journal, 2022)
The purpose of this paper is to explore the role of leader-member exchange (LMX) for selection-focused creativity. Thus, we seek to understand when subordinates develop high- quality relationships with their supervisors, do they also get their creative ideas validated by co-workers or not? The proposed model was tested using data obtained at two points in time from three data sources (co-workers, subordinates, and supervisors) working at a software solution provider operating in Pakistan. The obtained data were then analysed for random coefficient models with Mplus. It was found that having only quality LMX will not guarantee the validation of co-workers’ ideas. The focal employee needs to signal to others that they also care about their co-workers and have quality LMX. Subordinates who maintain quality relationships with their supervisors also need to consider what they signal to their co-workers by their behaviours and actions at work. Co-workers are more likely to provide support for creativity to those who are more supportive at work. We extend novel benefits associated with high-quality LMX, that is, the validation of co-workers’ ideas. Additionally, by focusing on social relationships for selection-focused creativity, we also extended creativity literature.